Effect of Roleplay Tabletop Disaster Simulation on Flood Preparedness Attitudes Among Junior High School Students - Prasetyawan, Riyan Dwi; Rudiyanto, Rudiyanto; Rahmawan, Fajri Andi; Rosuli, Ahmad; Rosiana, Angela Febiana Dewinta (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Disaster preparedness training is essential for junior high school children as a vulnerable group to increase awareness and preparedness for disasters. RTDS is an appropriate intervention in improving disaster preparedness. Objective: This study aims to determine the effect of tabletop roleplay disaster simulation on students' flood disaster preparedness attitude at SMPN 1 Muncar in 2024. Methods: A pre-experimental one-group pre-test and post-test design was used in this study, involving 30 respondents selected through a purposive sampling technique. A role-playing tabletop disaster simulation was used as the independent variable instrument to measure its effect on students' preparedness attitudes as the dependent variable. To measure the attitude of flood disaster preparedness in junior high school students using a questionnaire on the attitude of student preparedness in facing flood disasters. The questionnaire has been tested for validity and reliability. The data analysis method used is the Wilcoxon test. Results: The results of the analysis showed that after being given the Roleplay Tabletop Disaster Simulation (RTDS), students' disaster preparedness attitudes increased significantly. Before the intervention, 63.0% of respondents were in the low category, while after the intervention, 87.0% of respondents were in the very high category. Wilcoxon test showed that this difference was significant (P = 0.000 < 0.05), indicating the effect of RTDS on students' disaster preparedness. Conclusion: RTDS helps students understand safety procedures and improves their adaptability during disaster events.